Intersection of Race/Ethnicity and Socioeconomic Status in Mortality After Breast Cancer - Shariff-Marco, Salma (J Community Health, 2015)
We investigated social disparities in breast cancer (BC) mortality, leveraging data from the California Breast Cancer Survivorship Consortium. The associations of race/ethnicity, education, and neighborhood SES (nSES) with all-cause and BC-specific mortality were assessed among 9372 women with BC (diagnosed 1993–2007 in California with follow-up through 2010) from four racial/ ethnic groups [African American, Asian American, Latina, and non-Latina (NL) White] using Cox proportional hazards models. Compared to NL White women with high-education/high-nSES, higher all-cause mortality was observed among NL White women with high-education/ low-nSES [hazard ratio (HR) (95 % confidence interval) 1.24 (1.08–1.43)], and African American women with low-nSES, regardless of education [high education HR 1.24 (1.03–1.49); low-education HR 1.19 (0.99–1.44)]. Latina women with low-education/high-nSES had lower all-cause mortality [HR 0.70 (0.54–0.90)] and non-significant lower mortality was observed for Asian American women, regardless of their education and nSES. Similar patterns were seen for BC-specific mortality. Individual- and neighborhood-level measures of SES interact with race/ ethnicity to impact mortality after BC diagnosis. Considering the joint impacts of these social factors may offer insights to understanding inequalities by multiple social determinants of health.